Effect of Official Dollarization on Macroeconomic Performance and Money-Price Relationship in Ecuador - Selahattin Togay; Bedri Kamil Onur Taş (Turkish Economic Association, 2009)
This paper investigates effects of official dollarization on the macroeconomic performance of Ecuador using a time series perspective. More specifically, we investigate how dollarization effects inflation, GDP, inflation uncertainty and money-price relationship in Ecuador. There are four main findings of this study. First, inflation is lower after official dollarization. Second, GDP growth is higher after official dollarization when controlling for several other factors like rising oil prices and increase in the equity markets of emerging economies. Third, inflation uncertainty measured by inflation variance through GARCH is lower during official dollarization. Finally, money supply is endogenous after official dollarization and exogenous before official dollarization. As a result, we conclude that dollarization improved the macroeconomic performance of Ecuador and changed the money-price relationship in Ecuador.
Keywords: F31; E51; E42; E31; 330; Official Dollarization; Ecuador; Inflation uncertainty; GARCH model; Moneyprice relation; Endogeneity of money; Währungssubstitution; Makroökonomischer Einfluss; Zeitreihenanalyse; Inflation; Ecuador